A Study on Small and Medium-Sized Enterprises Perception Towards Islamic Banking Products - Shaharuddin, A.; Abdul Hamid, S.; Muda, M.; Yasmin Hanani Mohd Safian (Universiti Sains Islam Malaysia, 2024)
Small and Medium-Sized enterprises (SMEs) play an important supportive role in &e Malaysian economy. This research examines their perception towards the Islamic banking products offered by Islamic banking institutions. A total of 180 SMEs from the Federal Teritory of Kuala Lumpur, Selangor and Negeri Sembilan had been surveyed based on self-administered questionnaire. The results indicate that majority of the SMEs still do not consider the Islamic banks as the most desirable financia1 institution. The less effective marketing strategy has been identified as one of the reasons contributing to the low acceptance of products offered. The research concludes with some recommendations to be adopted in enhancing the effectiveness of lslamic banks marketing strategy.